Execution Mechanisms of Oragent -- An Organisation-Based Programming Language - Yin Chen; Xinjun Mao; Cuiyun Hu (2013 IEEE/WIC/ACM International Joint Conferences on Web Intelligence (WI) and Intelligent Agent Technologies (IAT), 2013)
The adoption of organisation-based agent-oriented programming has been quite limited, due to the lack of programming languages which are expressive enough to tackle the complexity brought by the dynamism of multi-agent systems. Oragent is an organisation-based agent-oriented programming language which provides explicit language primitives to program organisational concepts such as agents and groups as first-class entities, and to realise adaptation of multi-agent systems via role enactment and role-based interaction. In this paper, we present the execution mechanisms for Oragent language, which support adaptation of agent behaviour via role enactment, and role-based interaction among agents. A case study is presented to demonstrate the viability of these mechanisms.